2020
DOI: 10.1111/ppl.13225
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide potentiates defense system in presence of sulfur to protect chloroplast damage and photosynthesis of wheat under drought stress

Abstract: The involvement of hydrogen peroxide (H 2 O 2 ) combined with sulfur (S) was studied in the protection of the photosynthetic performance of wheat (Triticum aestivum L.) under drought stress. The mechanisms of S-assimilation, the activity of antioxidants, glucose sensitivity, water and osmotic relations and abscisic acid (ABA) content were the focus. The combined application of 50 μM H 2 O 2 and 100 mg S kg −1 soil (sulfur) resulted in a marked increase in S-assimilation and activity of antioxidant enzymes, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 69 publications
(118 reference statements)
1
19
0
Order By: Relevance
“…Having no statistical differences in physiological data for the baseline with no insects for all plants ( Table 1 ) helped ascertain that those initial conditions were similar for all the plants considered in the study, and no other stresses were present. Differences in physiological data after the introduction of insects in different treatments followed a variable pattern with not much difference for the photosynthetic rate (A), which is expected since plants compensate by either maintaining or increasing in some conditions A due to abiotic [ 40 , 41 ] or biotic stresses such as aphid attack [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Having no statistical differences in physiological data for the baseline with no insects for all plants ( Table 1 ) helped ascertain that those initial conditions were similar for all the plants considered in the study, and no other stresses were present. Differences in physiological data after the introduction of insects in different treatments followed a variable pattern with not much difference for the photosynthetic rate (A), which is expected since plants compensate by either maintaining or increasing in some conditions A due to abiotic [ 40 , 41 ] or biotic stresses such as aphid attack [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were some reports on the use of H 2 O 2 to improve seed germination. For example, H 2 O 2 application at suitable concentrations alleviated the inhibition of pistachio seed germination under salt stress [ 21 ]; reduced the oxidative damage to rape seedlings under low-temperature conditions [ 9 ]; and enhanced the growth of wheat and the efficiency of its antioxidant defense systems under drought stress [ 22 ]. Due to differences in crop varieties and treatment methods, the optimal concentration at which exogenous H 2 O 2 should be applied to alleviate NaCl stress is also diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Photosynthesis, a most basic physiological process, provide vital energy for various biological activities. Previous reports showed that drought can inhibit photosynthetic efficiency on maize [26,27], rice [28] , wheat [29] and other photosynthetic plants. In this study, a major number of genes related to Chl metabolism, light energy transfer and carbon fixation were significantly affected at the transcription level.…”
Section: Responses Of Photosynthetic System Involved In Drought Stressmentioning
confidence: 96%